Shawn Sheep the soccer star - Mirabella, Erin (VeloPress, 2008)
When Shawn behaves like his hero, Paul the Peacock, and acts like a star during a soccer game, he not only angers his teammates and disappoints his parents, he gets himself kicked out of the game.